STRATEGI PENDIDIKAN AGAMA ISLAM UNTUK MENGATASI DISORIENTASI IDENTITAS SISWA - Ijah Bahijah; Asep Mulyana (UI Cirebon (Universitas Islam Cirebon), 2025)
The phenomenon of identity disorientation among Muslim students in the digital era has become a serious challenge in religious education, especially for Islamic Religious Education (PAI) teachers who play a strategic role in maintaining the continuity of Islamic values. This study uses a qualitative approach with conceptual analysis and interviews with a PAI teacher in Depok District, Cirebon Regency, to explore strategies used in dealing with the Islamic identity crisis of students. The results of the study show two main effective strategies, namely the exemplary approach and the integration of Islamic values with the digital context and the daily lives of students. This strategy has a positive impact on strengthening students' religious character and spiritual understanding in the midst of socio-cultural changes. This research is important to strengthen the function of PAI as a media of value inheritance as well as an agent of social transformation in shaping the identity of the younger generation of Muslims in a relevant and contextual manner.